Protection of Maternity Rights of Women Workers in Makassar City: A Review of Islamic Law and the Implementation of the Labor Law - Nasir, Nurfainna; Mustafa, Zulhas’ari; Irianto, Afifah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
The main problems studied in this research are 1). How appropriate is the implementation of maternity rights for female workers in the city of Makassar? 2). What is the Islamic law analysis of the maternity rights of female workers in the city of Makassar. This research is included in the classification of field research, using a phenomenological approach. Data was obtained through interviews, observation and documentation methods. After that, the collected data was processed and analyzed in three stages, namely: data reduction, data collection, and drawing conclusions. The results of this research found indications of the suitability of the implementation of maternity rights for female workers in Makassar City, with Law Number 13 of 2003 concerning Employment. The implementation of the rights for menstrual leave, maternity leave, maternity leave and miscarriage leave in accordance with Article 81 paragraph (2) and Article 82 paragraph (1) is enforced by several companies in the city of Makassar, namely PT Indomarco, PT Sumber Alariyah Trijaya, PT Pertamina, PT Ruang Raya Indonesia. Apart from that, Islamic law views women as equal without any discrimination. Therefore, Islamic law regarding maternity care is seen as a fundamental right for a female worker who has a postpartum period that is three months long. This phase can be said to be a recovery period, meaning that for three months women are given time to rest after giving birth. The implication of this research is that it is hoped that corporate agencies will provide a private place for female workers, namely a place to breastfeed and express breast milk. And it is hoped that it will make it easier for female workers to obtain menstrual rights in the sense of not going through the administrative process.